Comparative study of visceral adiposity index and lipid profile with Body Mass Index in adolescent and young adults - Anusha, T.; Harsha, Y. Sree; Raju, D. S. S. K. (International Journal of Advances in Medicine, 2019)
Background: Obesity is associated with increased rate of mortality and morbidity if untreated. Obesity is a health hazard it required attention towards adolescent and adult age group. Generally, body fat is distributed into two main compartments that are subcutaneous adipose tissue and visceral adipose tissue. Waist Hip Ratio measures the subcutaneous adipose tissue, determination of visceral adiposity will further helpful for determination of cardiovascular disease. Methods: The study comprised of 120 subjects, of these adolescents comprised of 60 healthy adolescent childrens. The adults comprised of 60 healthy individuals. In all the subjects, Height was estimated in centimetres and Weight was measured in kilogram measured and BMI was calculated. The waist hip ratio and visceral adiposity index was calculated. In all the subjects, venous blood was collected from all the subjects for lipid profile estimation. Results: In present study BMI more than 25 have soon increased waist hip ratio and visceral adiposity index value than BMI less than 25 and it’s statically significant in both adolescent and adult group. It is also reported that BMI more than 25 have increased level of mean serum triglycerides, serum total cholesterol, LDL cholesterol and VLDL the increase was statistically significant. The mean serum HDL cholesterol was significantly decreased in BMI>25 group when compared with BMI<25. Conclusions: It was concluded that different age groups of adolescent and adult, appropriate methods should be planned specifically for adolescent and adult age group. Regular educational sessions are needed to make changes adolescent and adults toward obesity.